A community for students.
Here's the question you clicked on:
 0 viewing
anonymous
 4 years ago
How do you solve? 3x + 3y + 2z = –5
x + y + 3z = –4
2x + 2y + 5z = –7
anonymous
 4 years ago
How do you solve? 3x + 3y + 2z = –5 x + y + 3z = –4 2x + 2y + 5z = –7

This Question is Closed

anonymous
 4 years ago
Best ResponseYou've already chosen the best response.0can you set up the augmented matrix?

UnkleRhaukus
 4 years ago
Best ResponseYou've already chosen the best response.0add the second and third equations, and find the difference with the first equation, hence solve for z

anonymous
 4 years ago
Best ResponseYou've already chosen the best response.0or you can do matrices.

Callisto
 4 years ago
Best ResponseYou've already chosen the best response.23x + 3y + 2z = –5 (1) x + y + 3z = –4 (2) 2x + 2y + 5z = –7 (3) (2)x(2) + (2) 2 (x + y + 3z) + (2x + 2y + 5z) = 2(4) + (7) z = 1 z= 1 Sub z=1 into the equations. Solve x and y. If I haven't got that wrong, there should be infinitely many solutions for x and y. Sorry, I made a mistake in the deleted post.
Ask your own question
Sign UpFind more explanations on OpenStudy
Your question is ready. Sign up for free to start getting answers.
spraguer
(Moderator)
5
→ View Detailed Profile
is replying to Can someone tell me what button the professor is hitting...
23
 Teamwork 19 Teammate
 Problem Solving 19 Hero
 Engagement 19 Mad Hatter
 You have blocked this person.
 ✔ You're a fan Checking fan status...
Thanks for being so helpful in mathematics. If you are getting quality help, make sure you spread the word about OpenStudy.